Combined Photosensitization and Vaccination Enable CD8 T-Cell Immunity and Tumor Suppression Independent of CD4 T-Cell Help - Varypataki, Eleni Maria; Hasler, Fabio; Waeckerle-Men, Ying; Vogel-Kindgen, Sarah; Høgset, Anders; Kündig, Thomas M.; Gander, Bruno; Halin, Cornelia; Johansen, Pål (Frontiers in Immunology, 2019)
Cytotoxic T lymphocytes (CTLs) are key players in fighting cancer, and their induction is a major focus in the design of therapeutic vaccines. Yet, therapeutic vaccine efficacy is limited, in part due to the suboptimal vaccine processing by antigen-presenting cells. Such processing typically takes place via the MHC class II pathway for CD4 T-cell activation and not MHC class I pathway for activation of CD8 CTLs. We show that a combination of skin photochemical treatment and immunisation, so-called photochemical internalisation (PCI) facilitated CTL activation due to the photochemical adjuvant effect induced by photosensitiser, oxygen, and light. Mice were immunised intradermally with antigen and photosensitiser, followed by controlled light exposure. PCI-treated mice showed strong activation of CD8 T cells, with improved IFN- production and cytotoxicity as compared to mice immunised without parallel PCI treatment. Surprisingly, the CD8 T-cell effector functions were not impaired in MHC class II- or CD4 T-cell-deficient mice. Moreover, PCI-based vaccination caused tumour regression independent of MHC class II or CD4 T cells presence in melanoma bearing mice. Together the data demonstrate that PCI can act as a powerful adjuvant in cancer vaccines, even in hosts with impaired T-helper functions.